O sistema de partidos políticos na ordem jurídica constitucional democrática - Sá, Fabiana Costa Lima de (2002)
This dissertation researches the system of political parties in the legal constitutional democratic order. The compliance of the different parties with the constitutional democratic order was studied. The main objective was to analyse whether the political parties, with their vices, violate or not the Democratic State of Law. It was observed that generally, political parties are oligarchic and open to subomation. Their programs are not fulfilled by those elected; they are imprecise, that is, they are incapable of guiding govemment action and are not democratically drawn up. In view of these facts, it was concluded that currently political parties are not fulfilling their function in the perfecting of democracy; they break democratic principles in their organization and structure, therefore they are not, on the whole, defending the Democratic State-of Law.